Comparative cryopreservation of bovine and porcine primary hepatocytes - Andres, Sandra; Bartling, Babett; Stiensmeier, Vera; Starke, Alexander; Schmicke, Marion (Frontiers in Veterinary Science, 2023)
The isolation of primary hepatocytes from liver tissue of farm animals yields a very high number of cells, and a part of them can be stored by cryopreservation for future experiments. As no experience exists with the cryopreservation of hepatocytes from cattle, our study aimed at the cryopreservation of bovine hepatocytes by use of different protocols compared with the cryopreservation of hepatocytes from pig.We tested different freezing media (William's Medium E vs. University of Wisconsin solution), cryoprotectants (dimethyl sulfoxide with vs. without trehalose as additional additive), freezing systems (standard freezing container vs. controlled-rate freezer) and freezing times (4 vs. 28 d).These tests identified a general influence of species and freezing systems, whereas the influence of freezing media, trehalose additive and freezing time was less or not obvious. In this regard, we determined a mean recovery of 30 % of bovine hepatocytes and 55 % of porcine hepatocytes cryopreserved in a controlled-rate freezer, whereas the rates were about 10 % less when hepatocytes were frozen in a standard freezing container. In accordance with this observation, the cultivation of cryopreserved hepatocytes from cattle was less effective than that of porcine hepatocytes.Hepatocytes from cattle can be successfully cryopreserved and partially cultured after cryopreservation but with lower percentage than porcine hepatocytes.